Comparative study of walnut and pumpkin seeds oils biological value and oxidative stability - Nosenko, Tamara; Korolyuk, Tamara; Usatyuk, Svitlana; Vovk, Hanna O.; Kostinova, Tetiana (My University, 2019)
The work is devoted to the study of the biologically active components content and the oxidation stability of oils from non-traditional raw materials such as walnuts and pumpkin seeds. The content of phospholipids, carotenoides, chlorophylls, tocopherols and sterols as well as fatty acids and tocopherol homologues composition, acidity and oxidation stability of walnut and pumpkin seeds oils were determined. The walnut and pumpkin oils contain a significant amount of polyunsaturated fatty acids, in particular, the walnut oil contains linolenic acid and has close to the recommended ratio of ω-3: ω-6 polyunsaturated fatty acids. The linoleic (polyunsaturated, ω-6) and oleic (monounsaturated) fatty acids were dominated in fatty acids composition of pumpkin oil, the sum of saturated fatty acids was three times higher than in walnut oil. The important property of walnut oil is very high ratio of ω-3:ω-6 polyunsaturated fatty acids, that was 1:5 almost the same as recommended by dietologists for human diet. The difference of total tocopherols content of two oil samples was slight, but tocopherol homologues composition was very distinctive, that is the β-tocopherol was the main in the walnut oil and α-tocopherol − in the pumpkin seeds oil, respectively. Acidity of investigated samples of oils have increased sufficiently fast, reaching the value close to 4 mg KOH/g of oil during the 63 and 70 days for walnut and pumpkin seeds oils, respectively. Oxidative stability of two oil samples were estimated as peroxide value changes during 98 days of oil storage. It was shown that the induction period of walnut oil oxidation, measured as peroxide value increase initiation, was 56 days, inspite of high content of polyunsaturated fatty acid content and particularly linolenic acid in this oil. Duration of induction period of pumpkin seeds oil oxidation and shelf life were 70 and 98 days, respectively, while shelf life of walnut oil was about 90 days. The higher resistance of pumpkin oil to oxidative damage is primarily due to the fatty acid composition of this oil, namely to the high content of saturated and monounsaturated fatty acids and almost twice lower content of polyunsaturated fatty acids compared to the walnut oil. Both oils can be recomended as a valuable source of polyunsaturated fatty acids, antioxidants and vitamins for human nutrition.
Keywords: кафедра експертизи харчових продуктів; кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів; walnut oil; pumpkin seeds oil; tocopherols; antioxidants; oxidative stability; горіхова олія; гарбузова олія; токофероли; антиоксиданти; окиснювальна стійкість